A STUDY OF SEMANTIC SHIFT (SLANG) IN LANGUAGE ENGLISH - Yuni Lutfiah; Evina Septiani; Aidil Syah Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This research explores the semantic shifts occurring in English slang, examining both historical and contemporary examples to understand the underlying mechanisms and sociocultural factors driving these changes. Semantic shifts, particularly in slang, involve the alteration of word meanings due to various influences, including social interactions, media exposure, cultural exchange, and significant societal events. Through a literature review, the study investigates how slang terms evolve over time, focusing on the role of social media platforms in accelerating these shifts. Key mechanisms identified include the blending and shortening of words (shashification), distributional modelling for semantic change detection, and the impact of global and cultural exchanges. The study also highlights the influence of media and influential figures in popularizing new slang, as well as the role of technological advancements in facilitating rapid semantic evolution. The findings underscore the importance of understanding slang not only as a linguistic phenomenon but also as a reflection of broader societal and cultural shifts.